Study on medication prescription in the elderly population: benzodiazepine use and potential drug interactions - Mariana Macedo Alvim; Danielle Teles da Cruz; Glenda de Almeida Aquino; Isabel Cristina Gonçalves Leite (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2021)
Abstract Background Prescription of medications for elderly individuals is complex, potentially involving polypharmacy, drug interactions, and inappropriate medication. Notable among the medications are benzodiazepines, whose long-term use is common and growing among the elderly population. Objective This study aimed to evaluate the occurrence of potential drug interactions (PDI) in elderly community-dwelling patients who use benzodiazepines. Method Cross-sectional study, conducted via household survey, with 73 elderly persons in Juiz de Fora, MG, Brazil. The search and classification of PDIs was carried out using the Micromedex® system. Results The prevalence of benzodiazepine use in this population was 18.3% (95% CI, 15.2-21.6). The use of benzodiazepines was associated with polypharmacy (p<0.01; PR 3.03; 95% CI, 1.79-5.26). A total of 157 PDI occurrences were found in 69.9% of the elderly people assessed. Of these, 25 were related to benzodiazepines. In the elderly individuals who use benzodiazepines, polypharmacy was associated with PDI (p<0.01; PR = 16.13; 95% CI, 4.67-55.55). PDI occurrence was high in the elderly people who use benzodiazepines, including interactions of highly significant clinical value. Conclusion In general, PDI is associated with polypharmacy, which demonstrates the need to rationalize drug use in the elderly population through continuous monitoring, seeking the simplest and safest possible therapeutic regimen.